Influence of physical motor activity on the level of catecholamine secretion - Labinsky, Andriy; Labinska, Galina (Journal of Education, Health and Sport, 2017)
Topicality. Determination of the level of efficiency of physical culture classes according to the study of catecholamine excretion to find out the role of physical activity in the activity of a certain level of integration of the neuroendocrine system in the body’s adaptive processes. Objectives of the study: to study the content of catecholamines in the daily urine of groups of people who were engaged and those who were not engaged in physical culture by chromatographic method – to compare the results of the study to substantiate the relevance of research on the regularities of sympatho-adrenal system responses to various environmental factors. Research results.. Changes in the content of adrenaline, including its reduction in the urine of the main group in the dynamics and a slight increase in the content of dopamine in the urine compared with the control group testify of involving the exchange of catecholamines in the regulatory mechanisms of various physiological processes. A statistically significant higher level of adrenaline excretion and a decrease in the excretion of other catecholamines in the urine of the main group of subjects, and a better overall subjective state of the main group indicates a significant effect of physical culture on the establishment of neurotransmitter balance, possibly due to activation of neurohormone synthesis. Conclusions. Physical training and sufficient motor activity have a positive effect on the production and excretion of catecholamines and the establishment of an optimal neurotransmitter balance to improve adaptive processes in the human body